PERAN GURU DALAM MEMBANGUN KEMANDIRIAN ANAK ERA MODERN DI PENDIDIKAN ANAK USIA DINI KASIH IBU DESA RAMBUTAN MASAM KECAMATAN MUARA TEMBESI KABUPATEN BATANGHARI - Kaila Syahira; Mahluddin; Husin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early childhood independence is a crucial developmental aspect that does not develop naturally but requires optimal stimulation from teachers. This study aims to examine the teacher's role in building children's independence in the modern era at Pendidikan Kasih Ibu, Muara Tembesi District, identify the obstacles faced, and describe the efforts made to overcome them. This research employs a qualitative descriptive method. Data were collected through observation, interviews, and documentation with the principal and teachers as subjects. Data analysis involved reduction, presentation, and conclusion drawing, with validity ensured through triangulation. The results indicate that teachers play key roles as role models, facilitators, technology users, and collaborators with parents. Independence is fostered through habituation, modeling, and providing opportunities for independent activities. Obstacles include children's dependency, inconsistent parenting patterns, and teachers' limited digital skills. Efforts to overcome these challenges include habituating simple daily tasks, granting children the freedom to choose, and strengthening cooperation with parents to ensure consistency between school and home environments.